Perlindungan Data Pribadi dalam Era Digitalisasi dan Tantangan Keamanan Siber di Indonesia - MUHAMMAD RENDI; Fristia Berdian Tamza; Ahmad Irzal Fardiansyah (Jurnal Hukum Lex Generalis, 2025)
The digital era has brought fundamental transformations in personal data management in Indonesia, yet also presents increasingly complex security challenges. The incident of 341,000 Polri personnel data leaks by an actor named Bjorka in October 2025 provides concrete evidence of vulnerabilities in Indonesia's national cybersecurity infrastructure. Although Law Number 27 of 2022 on Personal Data Protection has been enacted as the primary legal instrument, its practical effectiveness still faces various structural and implementation obstacles.This research employs a normative juridical approach utilizing Lawrence M. Friedman's legal system framework to analyze weaknesses in three main pillars: institutional structure, regulatory substance, and data security culture. The analysis demonstrates that preventing data breaches requires a comprehensive approach integrating legal, technological, organizational, and cultural aspects. Policy recommendations are formulated for four key stakeholders—Government, Polri, Private Sector, and Society—to strengthen personal data protection governance and national cybersecurity in a sustainable manner.